Pengelolaan Perencanaan dan Manajemen Keuangan STT (Skaa Truna-Truni) Sadhara Bhakti Dusun Karang Lamper - Yaksa, I Wayan Wira Ady; Habibi, Habibi; Kusumasanthi, Dewi; Yasa, I Komang Widya Purnama (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to improve the capacity of financial management and activity planning at Skaa Truna-Truni (STT) Sadhara Bhakti, Karang Lamper Hamlet, Jagaraga Indah Village, Kediri District, West Lombok Regency. The main problems faced by the organization include unstructured financial records, low transparency, and weak accountability in managing organizational funds. The implementation method uses a participatory training and mentoring approach by integrating the Asset-Based Community Development (ABCD) and Community-Based Financial Education (CBFE) models. The activity is carried out through four stages, namely: 1) problem identification; 2) program preparation; 3) training and mentoring; and 4) evaluation. The results of the activity implementation show a significant increase in participants' financial literacy (from 56% to 86%), budget planning skills (from 48% to 83%), and financial recording accuracy (from 42% to 81%). Scientific findings reveal that improving financial literacy plays a crucial role in building a culture of accountability, while implementing simple digital systems improves reporting efficiency and organizational transparency.